1996
DOI: 10.1159/000217991
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cathepsin-D and pS2 Protein Levels in Human Breast Cancer Cell Lines

Abstract: Cathepsin-D and pS2 are two estrogen-regulated proteins in human breast cancer cell lines. They have been considered possible prognostic factors in breast cancer, but results have been contradictory. To better understand the regulation of these proteins, we investigated the role of estradiol (E2), serum, and growth factors in hormone-dependent (MCF-7, ZR75.1) and hormone-independent (MDAMB-231, BT20) breast cancer cell lines. E2 treatment in serum-free conditions increased intracellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A menstrual cycle-dependent expres-sion of pS2 was observed, while cathepsin D as well as estrogen receptor status was not modified [Khan et al, 1997], indicating a possible differential estrogen regulation of the two proteins [Rajah et al, 1996]. Indeed, previous results indicated that estrogen treatment of hormone-responsive cells (MCF7 and ZR75.1) increased intracellular and secreted pS2 levels in both lines and intracellular (MCF7, ZR75.1) and secreted (ZR 75.1) levels of cathepsin D, indicating further a differential regulation of production and/or secretion [Cappelletti et al, 1996]. This differential regulation was further indicated by the results of the present study.…”
Section: Discussionmentioning
confidence: 93%
“…A menstrual cycle-dependent expres-sion of pS2 was observed, while cathepsin D as well as estrogen receptor status was not modified [Khan et al, 1997], indicating a possible differential estrogen regulation of the two proteins [Rajah et al, 1996]. Indeed, previous results indicated that estrogen treatment of hormone-responsive cells (MCF7 and ZR75.1) increased intracellular and secreted pS2 levels in both lines and intracellular (MCF7, ZR75.1) and secreted (ZR 75.1) levels of cathepsin D, indicating further a differential regulation of production and/or secretion [Cappelletti et al, 1996]. This differential regulation was further indicated by the results of the present study.…”
Section: Discussionmentioning
confidence: 93%
“…This could be related to an enriched population of stem cells, as NCAM and sVCAM-1 are known to be related to neural stem cell survival, proliferation, and migration ( Shan, 2013 ; Klein et al, 2016 ), whereas increases in the protease cathepsin D are associated with improved amyloid beta clearance ( Gao et al, 2020 ; Kim et al, 2020 ). This effect could also be related to hNSC secretion of IGF-1, shown to promote survival of NCAM-expressing neural progenitors ( Gago et al, 2003 ; Monzo et al, 2013 ), which can mediate and induce cathepsin D expression ( Cappelletti et al, 1996 ; Wang et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%